2002
DOI: 10.4269/ajtmh.2002.67.684
|View full text |Cite
|
Sign up to set email alerts
|

The serum resistance-associated gene as a diagnostic tool for the detection of Trypanosoma brucei rhodesiense.

Abstract: Abstract. In the search for new diagnostic methods that would distinguish Trypanosoma brucei rhodesiense from T. b. brucei and T. b. gambiense, we have developed two polymerase chain reaction (PCR) primer sets. The first primer set was derived from the serum resistance−associated (SRA) gene of T. b. rhodesiense that confers resistance to lysis by normal human serum (NHS). The specificity of the SRA-based PCR was tested on 97 different trypanosome populations originating from various taxonomic groups, host spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
131
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(134 citation statements)
references
References 26 publications
1
131
0
2
Order By: Relevance
“…This PCR test is based on the assumption that human serum resistant trypanosomes have the sra gene and non-human infective trypanosomes do not which appears to hold true for the majority of isolates tested from east and southern Africa Welburn et al 2001;Agbo et al 2003), but not for west and central Africa (Berberof et al 2001;Radwanska et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This PCR test is based on the assumption that human serum resistant trypanosomes have the sra gene and non-human infective trypanosomes do not which appears to hold true for the majority of isolates tested from east and southern Africa Welburn et al 2001;Agbo et al 2003), but not for west and central Africa (Berberof et al 2001;Radwanska et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, while it is clear that the sra gene is responsible for human infectivity in a large number of T. b. rhodesiense isolates Welburn et al 2001), there are exceptions to this in trypanosome lines from East Africa (Rifkin et al 1994;Agbo et al 2003) and, critically, this gene is not present in West African T. b. gambiense isolates (De Greef and Hamers 1994;Radwanska et al 2002). Thus there must be alternative mechanisms determining human infectivity/human serum resistance other than those based on the sra gene.…”
Section: Introductionmentioning
confidence: 99%
“…These are PCR based, targeting the serum resistanceassociated (SRA) gene that is specific for T. b. rhodesiense (4,6,14) or the T. b. gambiense surface glycoprotein (TgSGP) that is specific for that subspecies (2,15). The need for specialized equipment and a constant supply of electricity has hindered integration of those techniques into the diagnostic algorithm.…”
mentioning
confidence: 99%
“…Although compelling evidence supports the role of SRA in human infectivity by T. b. rhodesiense, several investigators have reported the occurrence of human serum-resistant lines of African trypanosomes that lack the SRA gene (2,47,66,67). To investigate the mechanism of SRA-independent resistance, we generated human serum-resistant lines of T. b. brucei 427 (MiTat 1.2) by repeated in vitro exposure to human HDLs.…”
Section: Discussionmentioning
confidence: 99%
“…Several experiments have shown a correlation between the expression of the SRA gene and resistance to human serum (11,35), and transfection of this gene into T. b. brucei conferred resistance to human serum and TLF (41,74). In addition, the SRA gene has proven to be a reliable marker for T. b. rhodesiense in epidemiological studies throughout East Africa (16,18,39,47,72,73).…”
mentioning
confidence: 99%